1997
DOI: 10.1116/1.580706
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for covalent attachment of purple membrane to a gold surface via genetic modification of bacteriorhodopsin

Abstract: The objective of this work is to covalently attach bacteriorhodopsin (BR) to a gold surface via genetic substitution of cysteine for serine (S35C) at the 35th amino acid position. Samples of BR-containing purple membrane (PM) on gold were evaluated using atomic force microscopy (AFM) and x-ray photoelectron spectroscopy (XPS). AFM images reveal a surface coverage of S35C-containing PM fragments of approximately 25%. XPS measurements reveal a small excess of sulfur for S35C-containing PM on gold, and a much lar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…All the GBP sequences to date have contained methionine. The experimental literature is inconclusive as to whether methionine can form a covalent bond to gold [9,10]; however, because the protein was released from the surface in the presence of a detergent, and because other polypeptides containing methionine did not bind to gold, it is unlikely that the methionine sulfur contributes to the binding. Whereas many proteins and self-assembled monolayers bind to gold via disulfide bonds [11,12,13] the nature of GBP binding is thought to differ from this well-known thiol linkage and offer a new avenue for protein-gold surface interaction.…”
Section: Introductionmentioning
confidence: 96%
“…All the GBP sequences to date have contained methionine. The experimental literature is inconclusive as to whether methionine can form a covalent bond to gold [9,10]; however, because the protein was released from the surface in the presence of a detergent, and because other polypeptides containing methionine did not bind to gold, it is unlikely that the methionine sulfur contributes to the binding. Whereas many proteins and self-assembled monolayers bind to gold via disulfide bonds [11,12,13] the nature of GBP binding is thought to differ from this well-known thiol linkage and offer a new avenue for protein-gold surface interaction.…”
Section: Introductionmentioning
confidence: 96%
“…Recently, the hydration of a commercial ion-exchange membrane, Nafion, was studied with two complementary techniques: AFM and smallangle X-ray scattering; both techniques indicated that the number density of ionic clusters changes as a function of water content (22,23). On the other hand, the combined use of XPS and AFM allows the characterization of porous Nylon membranes coated with a crosslinked polysiloxane and modified by exposure to ultraviolet light (24); both techniques were also applied to study purple membranes deposited on gold (25).…”
Section: Introductionmentioning
confidence: 99%
“…In order to investigate the role played by these residues on the electron transfer to P450 cam , and to facilitate its immobilisation on the electrode surface, we have carried out site‐directed mutagenesis to modify the surface of this enzyme. Cysteine residues were chosen to replace these four basic residues based on the considerations that: (1) thiols show a strong affinity towards a gold surface and the genetic variants could be immobilised in a specific orientation [17,18], and (2) cysteines react readily with the maleimide moiety under physiological conditions and redox‐active labels could be attached on the surface of the enzyme at a desired location.…”
Section: Introductionmentioning
confidence: 99%